Efektivitas Konseling Keluarga Berencana Terhadap Minat Penggunaan Metode Kontrasepsi Jangka Panjang - Kurnia Mariatul Qiftih; Rosmiati Rosmiati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The Family Planning (FP) program is a strategic effort to control population growth and improve maternal and child health. Long-term contraceptive methods (LMPs), such as intrauterine devices (IUDs), implants, and sterilization, have been proven to be more effective and efficient than short-term methods. However, the use of LMPs remains relatively low. One factor contributing to the low use of LMPs is a lack of understanding and interest among couples of childbearing age due to limited information. This study aims to determine the effectiveness of family planning counseling on interest in using long-term contraceptive methods. The research method used was a quantitative approach with a pre-experimental design. The results showed that family planning counseling significantly increased interest in using LMPs. Therefore, high-quality and continuous family planning counseling is crucial for increasing the use of LMPs.